Public Opinion Toward Green Infrastructure On Buildings For Sustainable In Parit Buntar And Sungai Jawi - Saleh, Afza (Universiti Sains Malaysia, 2021)
During rainy seasons, a few places in Parit Buntar and Sungai Jawi are prone to flash floods. Local authorities must adopt environmental planning policies that can help create new green areas to achieve sustainable development goals and ensure a good quality of life for public, along with the rehabilitation of the natural environment. One of the ways to liven up green areas is by raising public awareness of the importance of green infrastructure. In order to effectively promote green infrastructure in Parit Buntar and Sungai Jawi, it is essential to comprehend public attitudes toward green infrastructure, so that suitable and effective strategies can be implemented by policy makers. In this study, one hundred thirty-three respondents were asked to provide their perception and awareness on green infrastructures. Questionnaire’s method was used for this survey, which was conducted through social media such as Facebook, WhatsApp and Telegram to facilitate respondents to answer the questions in their spare time and to prevent the transmission of covid 19. Data were analysed using SPSS for index mean, percentages and comparison between demographic factors and response of respondent on perception and awareness of green infrastructure. The results showed that the perception and awareness on green infrastructure are satisfactory. This aspect will help the local authority to increase the public awareness on green infrastructure. In addition, the results showed that no significant difference in the comparison of demographic factors on the questionnaire responses of the perception and awareness on green infrastructure aspect. This means that demographic factors do not affect any feedback given in this study.